2019
DOI: 10.47513/mmd.v11i4.707
|View full text |Cite
|
Sign up to set email alerts
|

Uncommon music making: The functional roles of music in design for healthcare

Abstract: In this paper, we discuss some uncommon settings and roles for music, demonstrating how music can aid in the design and implementation of socially responsible healthcare products that are encouraging, inclusive, and sensitive to critical contexts. We review three music-inspired design cases (CareTunes: Musical Alarms for Critical Care, Music and Senior Exercise, and We Are All Musicians and the Adaptive Use Musical Instrument) in which the authors took part. The literature review and the analysis of the case s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Tuuri and Eerola [ 2 ] emphasised the role of listening in the trajectory from perception to action and made a distinction between three sound-action couplings (AKA, sound-induced action as referred in our current study): We interpret their ‘action-sound-object’ as sound-induced action learnt by experience; ‘action-sound-intersubjectivity’ as sound-induced action interpreted differently by listeners; and ‘action-sound habit’ as predictable sound-induced actions in familiar situations. Research also highlighted the embodied responses towards heard sounds and thus exemplified reflexive actions such as altering bodily movement (e.g., altering walking sounds improves one’s gait; music guides (elderly) physical exercises) [ 66 , 67 , 68 ].…”
Section: Background Into Listening In Complex Sound Environmentsmentioning
confidence: 99%
“…Tuuri and Eerola [ 2 ] emphasised the role of listening in the trajectory from perception to action and made a distinction between three sound-action couplings (AKA, sound-induced action as referred in our current study): We interpret their ‘action-sound-object’ as sound-induced action learnt by experience; ‘action-sound-intersubjectivity’ as sound-induced action interpreted differently by listeners; and ‘action-sound habit’ as predictable sound-induced actions in familiar situations. Research also highlighted the embodied responses towards heard sounds and thus exemplified reflexive actions such as altering bodily movement (e.g., altering walking sounds improves one’s gait; music guides (elderly) physical exercises) [ 66 , 67 , 68 ].…”
Section: Background Into Listening In Complex Sound Environmentsmentioning
confidence: 99%
“…Another well-used app, Yousician 3 , offers various ways to learn a musical instrument, such as the guitar, at home through lessons and “serious games.” Mazaam 22 is an engaging and animated app for children that can increase their understanding of music and claims to improve their cognitive and/or motor skills through a range of music games and lessons. Another set of applications, intended to stimulate exercise in the elderly by creating novel instruments that can be played individually or together, was described in terms of the design process by Özcan et al (2019), similarly to the Jymmin’ application mentioned previously (Fritz et al, 2013). As the above examples of music technology are generally not used in the context of a rehabilitation program but rather at the initiative of individual users, many are not developed in an evidence-based manner, and their effects on health are not scientifically supported (although in the case of Jymmin’, a significant reduction of perceived effort is reported; see Fritz et al, 2013).…”
Section: Various Use Cases Of Music Technology In Health Settingsmentioning
confidence: 99%
“…Accordingly, there is sufficient evidence to use music and nature sounds as design interventions to be overlayed on PICU soundscapes so that these soundscapes are perceived to be more pleasant. The design space with music and natural sounds is vast [17]; yet, we are interested in preliminary findings on the efficacy of our design concept. Thus, we chose the following sounds which were used in earlier studies and shown to have positive effects on listeners: one sample from Mozart's Piano Concerto No.…”
Section: Introductionmentioning
confidence: 99%